2005
DOI: 10.1111/j.1365-3032.2005.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction of cues in the dust and frass of Prostephanus truncatus and analysis of behavioural mechanisms leading to arrestment of the predator Teretrius nigrescens

Abstract: Teretrius nigrescens is a predatory beetle released into Africa for classical biological control of Prostephanus truncatus, currently the most serious insect pest of stored maize on the continent. T. nigrescens is arrested by the dust and frass produced by P. truncatus boring into maize and it has been concluded that this effect is most likely to be caused by chemicals in the dust/frass. A bioassay is presented in which EthoVision software (Noldus Information Technology, the Netherlands) captures and analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Cues from the host and the host plant are present in the herbivore faeces and are used for host recognition in the system wheat- S. granarius - L. distinguendus (Steidle & Ruther, 2000). Stewart-Jones et al (2005) found that the predator Teretrius nigrescens spent more time in zones treated with extracts of dust and frass of Prostephanus truncatus than the zone to which an extract of maize flour had been applied. Further, they analyzed the extracts of maize flour and P. truncatus dust and frass, and they found that P. truncatus infestation increased the free fatty acid content in the dust and frass.…”
Section: Discussionmentioning
confidence: 99%
“…Cues from the host and the host plant are present in the herbivore faeces and are used for host recognition in the system wheat- S. granarius - L. distinguendus (Steidle & Ruther, 2000). Stewart-Jones et al (2005) found that the predator Teretrius nigrescens spent more time in zones treated with extracts of dust and frass of Prostephanus truncatus than the zone to which an extract of maize flour had been applied. Further, they analyzed the extracts of maize flour and P. truncatus dust and frass, and they found that P. truncatus infestation increased the free fatty acid content in the dust and frass.…”
Section: Discussionmentioning
confidence: 99%